Multi-omics reveals immune response and metabolic profiles during high-altitude mountaineering - Jianhua Yin; Jingzhi Lv; Shichen Yang; Yang Wang; Zhuoli Huang; Xue Wang; Guixue Hou; Wenwen Zhou; Ying Liu; Weikai Wang; Xiumei Lin; Yunting Huang; et al. (Cell Reports)
Summary: The physiological perturbations induced by high-altitude exposure in mountain climbers, manifesting as immunological and metabolic deviations, have been previously reported but are not fully understood. In this study, we obtain multi-omic profiles of climbers’ blood samples, including single-cell transcriptomic analysis of 375,722 immune cells, and plasma metabolomics and lipidomics. Longitudinal analysis reveals dynamic immune response profiles, during the acclimatization period, characterized by the downregulation of inflammatory responses in myeloid cell subsets and by the enhancement of immune effector processes in cytotoxic CD8+ T, γδT, and CD16+ natural killer cells. In contrast, during extreme-altitude mountaineering, the activation of inflammatory responses and impairment of immune effector function are observed, concomitant with an increased cellular response to hypoxia and oxidative stress pathways. Furthermore, glycolysis and antioxidant gene expression are upregulated during extreme-altitude mountaineering. Plasma metabolic analysis reveals significant alterations, involving enhanced glutamine and fatty acid metabolism.